Lenient rate control versus strict rate control for atrial fibrillation: a protocol for the Danish Atrial Fibrillation (DanAF) randomised clinical trial - Janus Christian Jakobsen; Christian Gluud; Emil Eik Nielsen; Joshua Buron Feinberg; Michael Hecht Olsen; Axel Brandes; llan Raymond; Walter Bjørn Nielsen; Frank Stensgaard-Hansen; Ulrik Dixen; Ole Dyg Pedersen; Uffe Jakob Ortved Gang (BMJ Open)
Introduction Atrial fibrillation is the most common heart arrhythmia with a prevalence of approximately 2% in the western world. Atrial fibrillation is associated with an increased risk of death and morbidity. In many patients, a rate control strategy is recommended. The optimal heart rate target is disputed despite the results of the the RAte Control Efficacy in permanent atrial fibrillation: a comparison between lenient vs strict rate control II (RACE II) trial.Our primary objective will be to investigate the effect of lenient rate control strategy (<110 beats per minute (bpm) at rest) compared with strict rate control strategy (<80 bpm at rest) on quality of life in patients with persistent or permanent atrial fibrillation.Methods and analysis We plan a two-group, superiority randomised clinical trial. 350 outpatients with persistent or permanent atrial fibrillation will be recruited from four hospitals, across three regions in Denmark. Participants will be randomised 1:1 to a lenient medical rate control strategy (<110 bpm at rest) or a strict medical rate control strategy (<80 bpm at rest). The recruitment phase is planned to be 2 years with 3 years of follow-up. Recruitment is expected to start in January 2021. The primary outcome will be quality of life using the Short Form-36 (SF-36) questionnaire (physical component score). Secondary outcomes will be days alive outside hospital, symptom control using the Atrial Fibrillation Effect on Quality of Life, quality of life using the SF-36 questionnaire (mental component score) and serious adverse events. The primary assessment time point for all outcomes will be 1 year after randomisation.Ethics and dissemination Ethics approval was obtained through the ethics committee in Region Zealand. The design and findings will be published in peer-reviewed journals as well as be made available on ClinicalTrials.gov.Trial registration number NCT04542785.